Preparation of cerium (III) carbonate dispersion

By preparing the aqueous dispersion of nanoscale cerium (III) carbonate particles, the problem of color stability and gloss reduction in the external paint is solved, and better color retention and durability are achieved.

CN115605434BActive Publication Date: 2025-02-11RGT UNIV OF CALIFORNIA +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180022269.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-20
Filing Date
2021-02-09
Publication Date
2025-02-11
Estimated Expiration
2041-02-09

AI Technical Summary

Technical Problem

In the field of exterior paint, it is difficult for the prior art to effectively maintain color stability and gloss, especially when using TiO2 as an opaque pigment, color fading and undesirable color formation due to its colorant degradation under UV light.

Method used

By preparing an aqueous dispersion of nanoscale cerium (III) carbonate particles, mixing water-soluble cerium (III) salt, water-soluble carbonate and capping ligands (such as amine carboxylic acid or salts thereof) in water to form a 100% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20% 20 Cerium (III) carbonate particles in a specific particle size range, thus serving as a stabilizing and protective effect in the coating.

Benefits of technology

This method significantly improves color retention capabilities, reduces undesired color formation, and extends the durability of the coating, especially under UV light exposure conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for preparing an aqueous dispersion of nanometer-sized cerium (III) carbonate particles, comprising mixing a) a water-soluble cerium (III) ammonium salt, b) a water-soluble carbonate, and c) a capping ligand in water to form an aqueous dispersion of cerium (III) carbonate particles having a resulting z-average particle size in the range of 5 nm to 500 nm. The method is used to prepare an additive for use in a formulation comprising a polymer, a pigment, a dye, or a toner, or a combination thereof, to promote color retention and reduce undesirable color formation in a coating formed by these formulations.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citations of Related Applications

[0002] This application claims priority to U.S. Provisional Application No. 62 / 992,393, filed on March 20, 2020. Background Art

[0003] In the field of exterior paints, it is desirable to have a paint-coated substrate that maintains a fresh appearance over an extended period of time. This "freshly painted" appearance can be measured by three interrelated properties: dirt-pickup resistance (DPUR), gloss retention, and tintretention. Of these, tintretention is particularly important as darker and deeper colors become more popular in exterior applications.

[0004] The loss of hue retention, also known as fading, is believed to be caused by photocatalytic polymer-mediated and colorant degradation by TiO2, which is used as an opaque pigment in most paint formulations. TiO2 particles absorb UV light and, in the presence of water, generate highly reactive hydroxyl groups that reactively degrade the polymer backbone and colorant, causing gloss loss, fading, and undesirable color formation.

[0005] The attempt to mitigate the degradation of external coatings has been largely achieved by using UV absorbers to prevent free radical formation and antioxidants to quench free radicals by blocking UV light before polymer or colorant degradation occurs. Unfortunately, UV absorbers require sufficiently long path lengths for absorption and are therefore only effective in transparent top coatings. Antioxidants (such as hindered amines, hindered phenols, carbon-centered free radicals, phosphites, and sulfides) tend to leach from the coated substrate, thus only providing short-term protection. Therefore, it would be advantageous to find more effective ways to achieve color retention and reduce undesirable color formation in the coated surface in the field of external coatings. Summary of the invention

[0006] The present invention solves the need in the art by providing a method for preparing an aqueous dispersion of nanometer-sized cerium (III) carbonate particles, the method comprising the steps of mixing in water a) a water-soluble ammonium cerium (III) salt, b) a water-soluble carbonate, and c) a capping ligand, wherein the capping ligand is an amine carboxylic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof; wherein the relative proportions of a), b), and c) are such that the z-average particle size of the resulting cerium (III) carbonate particles is in the range of 5 nm to 500 nm. DETAILED DESCRIPTION

[0007] In a first aspect, the present invention is a method for preparing an aqueous dispersion of nanoscale cerium (III) carbonate particles, the method comprising the steps of mixing in water a) a water-soluble ammonium cerium (III) salt, b) a water-soluble carbonate, and c) a capping ligand, wherein the capping ligand is an amine carboxylic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof; wherein the relative proportions of a), b), and c) are such that the z-average particle size of the resulting cerium (III) carbonate particles is in the range of 5 nm to 500 nm.

[0008] As used herein, "nanoscale cerium (III) carbonate particles" refers to cerium (III) carbonate particles having a z-average particle size of no more than 500 nm as measured by dynamic light scattering. The term "nanodispersion" refers to an aqueous dispersion of nanoscale cerium (III) carbonate particles. In another aspect, the nanoscale cerium (III) carbonate particles have a z-average particle size of no more than 300 nm; in another aspect, no more than 200 nm; in another aspect, no less than 50 nm.

[0009] As used herein, "water-soluble cerium (III) ammonium salt" refers to a cerium (III) ammonium salt that is at least 10% soluble in water in the proportion used. A preferred water-soluble cerium (III) ammonium salt is cerium (III) ammonium nitrate. Similarly, the term "water-soluble carbonate" refers to an alkali metal or ammonium carbonate or bicarbonate that is at least 10% soluble in water in the proportion used. Examples of water-soluble carbonates include sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate and potassium bicarbonate, with ammonium carbonate being preferred.

[0010] As used herein, "amine carboxylic acid" is a compound comprising at least one amine group and at least one carboxylic acid group. Preferably, the amine carboxylic acid is aminoacetic acid or a salt thereof; preferably, the aminoacetic acid comprises at least two carboxylic acid groups; more preferably, the aminoacetic acid is diacetamide, triacetamide, or tetraacetamide, examples of which include ethylenediaminetetraacetic acid (EDTA), ethylenediaminediacetic acid (EDDA), and nitrolotriacetic acid (NTA, nitrilotriacetic acid).

[0011] The polymer functionalized with carboxylic acid groups can be, for example, a homopolymer resulting from the homopolymerization of carboxylic acid-containing monomers such as acrylic acid, or a copolymer resulting from the copolymerization of carboxylic acid-containing monomers with one or more additional monomers (which do not require carboxylic acid functionalization). An example of a homopolymer functionalized with carboxylic acid groups is polyacrylic acid (PAA).

[0012] "Amine phosphonic acid" refers to a compound comprising at least one amine group and at least one phosphonic acid group. The end-capping ligand may include one or more phosphonic acids and one or more carboxylic acid groups, and salts thereof. Examples of amine phosphonic acids include aminotrimethylphosphonic acid (ATMP), 6-amino-2-[bis(carboxymethyl)amino]hexanoic acid, and N-(phosphonomethyl)iminodiacetic acid (PIDA).

[0013] A water-soluble cerium (III) ammonium salt (preferably ammonium cerium (III) nitrate), a water-soluble carbonate (preferably ammonium carbonate), and a capping ligand are advantageously mixed together in water at a pH in the range of 8 (preferably 9) to 12 (preferably 11) under conditions sufficient to produce a nano-dispersion of cerium (III) carbonate particles. The mole: mole ratio of the water-soluble cerium (III) ammonium salt to the water-soluble carbonate is preferably in the range of 2: 1, more preferably 1: 1 to preferably 1: 20, more preferably 1: 10; the mole: mole ratio of the water-soluble cerium (III) ammonium salt to the capping ligand is preferably in the range of 50: 1, more preferably 30: 1 to 1: 1. The reaction is typically carried out at or near ambient temperature, and the reaction is typically complete within one hour.

[0014] In another aspect, the present invention is a composition comprising an aqueous dispersion of cerium (III) carbonate particles having a z-average particle size in the range of 5 nm to 500 nm. The dispersion preferably also comprises a capping ligand, which is believed to promote the formation of nano-dispersed particles while stabilizing the particles to prevent aggregation.

[0015] Based on the weight of water and cerium (III) carbonate, the concentration of cerium (III) carbonate in water is preferably in the range of 0.2 wt %, more preferably 0.5 wt %, most preferably 1 wt % to 25 wt %, more preferably 21 wt %. More typically, the concentration of the reactants is adjusted to form a final dispersion of 1 to 5 wt % solids; compositions with higher solids content can be prepared by centrifugation, followed by removal of the supernatant or vacuum removal of water.

[0016] In another aspect, the present invention is a composition comprising a polymer and cerium carbonate (III) particles. In this respect, the polymer preferably forms a solution or dispersion with a liquid. In one embodiment of this aspect of the invention, the composition is an aqueous dispersion of polymer particles (latex) and cerium carbonate (III) particles. In this respect, the particle size of the dispersed cerium carbonate (III) particles is not limited. Larger cerium carbonate (III) particles, especially particles with a z-average particle size in the range of 2 μm to 20 μm as measured by DLS can be prepared substantially as described above, but without end-capping ligands.

[0017] Compositions comprising latex and cerium (III) carbonate particles are useful in the field of coating compositions, especially coating compositions comprising pigments or colorants or both. Pigments include opaque pigments and extenders. Opaque pigments include TiO2, BaSO4 and organic hollow sphere polymer particles (HSP). TiO2 can be anatase or rutile, and can be passivated or unpassivated. Commercial examples of TiO2 are Ti-Pure-R706 TiO2 and DeGussa P25 TiO2 photocatalysts. Compositions can include combinations of anatase and rutile, passivated and unpassivated TiO2.

[0018] Suitable extenders include carbonates, silicon dioxide, silicates, aluminosilicates, phosphates, and non-hollow organic microspheres. More specific examples of extenders include talc, clay, mica, sericite, CaCO3, nepheline, feldspar, wollastonite, kaolinite, dicalcium phosphate, and diatomaceous earth.

[0019] The colorant may be organic or inorganic, dispersible (tint) or soluble (dyes). Examples of suitable colorants include methylene blue, phthalocyanine blue, phthalocyanine green, monoarylide yellow, diarylide yellow, benzimidazolone yellow, heterocyclic yellow, DNA orange, pyrrole orange, quinacridone magenta, quinacridone violet, dioxazine violet, quinacridone red, naphthol red, pyrrole red, metallized azo red, nonmetallized azo red, carbon black, lampblack, black iron oxide, yellow iron oxide, brown iron oxide, and red iron oxide.

[0020] In another aspect, the invention is a composition comprising a polymer such as poly(methyl methacrylate) (PMMA) dissolved in a solvent such as chloroform in the presence of dispersed cerium (III) carbonate particles. The composition of this aspect of the invention is useful, for example, in the housing of an automotive headlamp.

[0021] In another aspect, the present invention is a composition comprising cerium (III) carbonate particles and a neat polymer. Such a composition can be prepared by mixing cerium (III) carbonate particles with an extruded polymer melt.

[0022] Examples of suitable polymers include polyacrylates, poly(styrene-acrylates), polystyrene, polyvinyl acetate, polyurethanes, poly(vinyl acetate-acrylates), silicones, epoxies, polyolefins, cellulose, and polysilicates.

[0023] Cerium (III) carbonate nanodispersions are particularly useful in applications such as latex paint formulations where color and gloss retention are desired.

[0024] Example 1-4 - Preparation of aqueous nanodispersion of cerium (III) carbonate particles

[0025] In the following examples, the z-average particle size was determined by dynamic light scattering.

[0026] Example 1 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by EDTA

[0027] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL of deionized water) was added to a 250 mL plastic bottle. EDTA (50 mg) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 seconds while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.

[0028] The product mixture was divided into four 40 mL centrifuge tubes and then centrifuged at 20,000 rpm for 6 min. The white product in each tube was collected and washed with 25 mL of water, including 5 min vortex mixing to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.

[0029] To study the effect of EDTA loading on the properties of cerium (III) carbonate, the example was repeated twice using 100 mg and 500 mg of EDTA. The z-average particle size of the cerium carbonate particles was found to be 125 nm (50 mg EDTA), 118 nm (100 mg EDTA), and 114 nm (500 mg EDTA).

[0030] Example 2 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by NTA

[0031] The procedure described in Example 1 was essentially followed except that NTA (65 mg) was used instead of EDTA as the capping ligand. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.

[0032] This example was repeated using 32.5 mg of NTA. The z-average particle size of the cerium (III) carbonate particles was found to be 157 nm (32.5 mg NTA) and 115 nm (65 mg NTA).

[0033] Example 3 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by PIDA

[0034] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL of deionized water) was added to a 250 mL plastic bottle. PIDA (72 mg) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 seconds while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.

[0035] The product mixture is divided into four 40mL centrifuge tubes and then centrifuged for 6min at 20,000rpm. The white product in each tube is collected and washed with 25mL water, including 5min vortex mixing to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation is obtained as a wet paste with 20wt% solid content. The z-average particle size of the cerium carbonate particles is found to be 105nm.

[0036] Example 4 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by PAA

[0037] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL of deionized water) was added to a 250 mL plastic bottle. PAA (500 mg of a 50% aqueous solution, MW = 2000 g / mol) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 s while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.

[0038] The product mixture was divided into four 40 mL centrifuge tubes and then centrifuged at 20,000 rpm for 6 min. The white product in each tube was collected and washed with 25 mL of water (including 5 min vortex mixing) to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.

[0039] The example was repeated twice using 1.1 g and 2.2 g of 50% aqueous PAA.The z-average particle size of the cerium carbonate particles determined by dynamic light scattering (DLS) was found to be 105 nm (0.5 g PAA), 105 nm (1.1 g PAA), and 20 nm (2.2 g NTA).

[0040] Example 5-7 - Preparation of coating formulations using dyes and hues

[0041] In the following preparation, the acrylic adhesive had the following characteristics: (49BA / 50MMA / 1MAA), z-average particle size = 98nm, solids content 40.2 wt.%.

[0042] Preparation of paint formulations using dyes:

[0043] Two separate dispersions were prepared as follows:

[0044] A. Ti-Pure-R706 TiO2 (3.5 g), optionally 10% DeGussa P25 TiO2 photocatalyst based on the weight of Ti-Pure-R706 TiO2, TAMOL TM 1124 dispersant (trademark of Dow Chemical Company or its affiliates, 0.3 wt. % relative to the weight of the pigment), 1 M NH4OH (10 μL) and 3.5 x 10 -4 Aqueous solution of M Congo red dye or methylene blue dye (0.7 mL) was mixed at 1700 rpm in the presence of ZrO beads (10 mm) to form a TiO slurry. The ZrO beads were removed from the slurry and then additional amounts of dye solution (1.27 mL) were added to the slurry over time. The mixture was then mixed (3500 rpm for 3 min) to obtain 4.65 g of a 75 wt.% pigment slurry.

[0045] B. Combine 2 wt.% to 5 wt.% solids of cerium (III) carbonate (relative to the weight of Ti-Pure-R706 in step A) (20% solids wet paste prepared as described above without or with a capping ligand, as described in Example 2) with water (0.86 mL to 0.44 mL, depending on the solids). The pH of the resulting solution was adjusted to pH 9 with 1 M NH4OH. The mixture was sheared (3500 rpm for 4 min) and then sonicated (10 min).

[0046] The slurry from step A was mixed with acrylic binder (12.79 g) under stirring. The dispersion from step B was mixed with the slurry from step A and the mixture was sheared (3500 rpm for 1 min). ACRYSOL TM 2020E thickener (a trademark of The Dow Chemical Company or its affiliates, 0.6 g) was added to the mixture and mixed (3500 rpm for 3 min) to obtain a final paint formulation at about 16% pigment volume concentration (PVC).

[0047] Preparation of paint formulations with tint:

[0048] Combine Ti-Pure-R706 TiO2 (4.6g), TAMOL TM 1124 dispersant (0.3 wt.% relative to the weight of the pigment), 1M NH4OH (10 μL), DeGussa P25 TiO2 photocatalyst (0.36 g), Colorprove organic red 808 colorant (0.44 g) and water (1.53 g) were mixed at 2100 rpm in the presence of ZrO2 beads. The ZrO2 beads were removed from the slurry and the slurry was mixed again (3500 rpm, 3 min) to obtain 7 g of 75 wt.% pigment slurry. The slurry was mixed with the dispersion described in step B (except that only cerium (III) carbonate was prepared according to Example 2) to form a final paint formulation with a PVC of about 16%.

[0049] UV-induced photodegradation of coatings

[0050] The paint formulation was applied to a polyacrylic acid substrate using a 3 mil bar applicator. The applied coating was dried under ambient conditions for 72 h. The dried coating was then irradiated under 254-nm UV light (140-150 Lux) for 4 h.

[0051] A portion of the coating (200 mg) was scraped off the polyacrylic acid substrate, combined with 1 mL of ethanol, and sonicated for 15 min. The mixture was then vortexed for 5 min, and the supernatant containing the residual dye was analyzed by UV-vis spectroscopy to determine the extent of dye degradation.

[0052] Example 5 - Dye degradation by UV-vis, containing P25

[0053] As described above, when a sample containing Ti-R706-TiO2, DeGussa P25, acrylic binder, Congo red dye and cerium (III) carbonate without a capping ligand was exposed to UV light, the degree of dye degradation was 8%. In contrast, the degree of degradation without cerium (III) carbonate was 40%.

[0054] Example 6 - Dye degradation by UV-vis without P25

[0055] As described above, when a sample containing Ti-R706-TiO2, acrylic binder, methylene blue dye and cerium (III) carbonate without a capping ligand was exposed to UV light, the degree of dye degradation was 0%. In contrast, the degree of degradation without cerium (III) carbonate was 15%.

[0056] Example 7 - Toner Degradation by UV-vis, Containing P25

[0057] As described above, when a sample containing Ti-R706-TiO2, DeGussa P25, an acrylic binder, an organic red tint, and cerium (III) carbonate with a capping ligand (as described in Example 2) was exposed to UV light, it was found that color retention was completely retained. In contrast, the sample without cerium (III) carbonate showed significant color loss.

[0058] UV-induced photodegradation of polymethyl methacrylate:

[0059] A mixture of a) PMMA dissolved in CHCl3 and b) cerium (III) carbonate particles (prepared as in Example 1 or 3; 2 or 5 wt.% based on the weight of PMMA) was poured into a watch glass and allowed to dry for 16 h under ambient conditions. After drying for 16 h, the PMMA film was then irradiated for 4 h under 254-nm UV light (140-150 Lux).

[0060] Example 8 - UV Photodegradation of PMMA with EDTA-capped Cerium(III) Carbonate

[0061] No yellowing was observed for the irradiated PMMA film containing cerium (III) carbonate capped with EDTA (2 wt % based on the weight of PMMA). In contrast, the cast film without cerium (III) carbonate exhibited significant yellowing.

[0062] Example 9 - UV Photodegradation of PMMA with PIDA-terminated Cerium(III) Carbonate

[0063] No yellowing was observed for the irradiated PMMA film containing cerium (III) carbonate end-capped with PIDA (5 wt % based on the weight of PMMA). In contrast, the cast film without cerium (III) carbonate exhibited significant yellowing.

[0064] These studies demonstrate that cerium (III) carbonate substantially improves discoloration in coatings prepared from the coating formulations and significantly reduces undesirable color formation.

Claims

1. A method for preparing an aqueous dispersion containing nano-sized cerium (III) carbonate particles, comprising the steps of mixing in water a) a water-soluble cerium (III) ammonium salt, b) a water-soluble carbonate, and c) a capping ligand, wherein the capping ligand is an amine carboxylic acid or a salt thereof, an amine phosphonic acid or a salt thereof, or a polymer functionalized with a carboxylic acid group or a salt thereof; wherein: The relative proportions of a), b), and c) are such that the z-average particle size of the resulting cerium (III) carbonate particles is in the range of 5 nm to 500 nm; wherein the aqueous dispersion is used to maintain color and gloss in the coating and avoid the formation of undesirable color.

2. The method according to claim 1, wherein: The water-soluble cerium (III) ammonium salt is cerium (III) ammonium nitrate.

3. The method according to claim 2, wherein: The water-soluble carbonate is sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate or potassium bicarbonate.

4. The method according to claim 2, wherein: The water-soluble carbonate is ammonium carbonate.

5. The method according to claim 4, wherein: The end-capping ligand is ethylenediaminetetraacetic acid or a salt thereof, ethylenediaminediacetic acid or a salt thereof, nitrilotriacetic acid or a salt thereof, polyacrylic acid or a salt thereof, aminotrimethylphosphonic acid or a salt thereof, 6-amino-2-[bis(carboxymethyl)amino]hexanoic acid or a salt thereof, or N-(phosphonomethyl)iminodiacetic acid or a salt thereof.

6. The method according to claim 4, wherein: The end-capping ligand is ethylenediaminetetraacetic acid or a salt thereof, ethylenediaminediacetic acid or a salt thereof, nitrilotriacetic acid or a salt thereof, polyacrylic acid or a salt thereof, or N-(phosphonomethyl)iminodiacetic acid or a salt thereof.

7. The method according to claim 3, wherein: The mole:mole ratio of the ammonium cerium (III) nitrate to the water-soluble carbonate is in the range of 2:1 to 1:

20.

8. The method according to claim 6, wherein: The mole:mole ratio of the ammonium cerium (III) nitrate to the ammonium carbonate is in the range of 1:1 to 1:10; and the mole:mole ratio of the ammonium cerium nitrate to the capping ligand is in the range of 50:1 to 1:1.

Citation Information

Patent Citations

  • Preparation method of cerium carbonate and cerium oxide

    CN102161497A

  • Ultraviolet-shielding agent, method for the preparation thereof and cosmetic composition compounded therewith

    US5478550A